Tracing genetic signatures of bat‐to‐human coronaviruses and early transmission of North American SARS‐CoV‐2. Issue 4 (28th May 2021) - Ou, Xumin; Yang, Zhishuang; Zhu, Dekang; Mao, Sai; Wang, Mingshu; Jia, Renyong; Chen, Shun; Liu, Mafeng; Yang, Qiao; Wu, Ying; Zhao, Xinxin; Zhang, Shaqiu; et al.
Abstract: Highly pathogenic coronaviruses, including SARS‐CoV‐2, SARS‐CoV and MERS‐CoV, are thought to be transmitted from bats to humans, but the viral genetic signatures that contribute to bat‐to‐human transmission remain largely obscure. In this study, we identified an identical ribosomal frameshift motif among the three bat–human pairs of viruses and strong purifying selection after jumping from bats to humans. This represents genetic signatures of coronaviruses that are related to bat‐to‐human transmission. To further trace the early human‐to‐human transmission of SARS‐CoV‐2 in North America, a geographically stratified genome‐wide association study (North American isolates and the remaining isolates) and a retrospective study were conducted. We determined that the single nucleotide polymorphisms (SNPs) 1, 059.C > T and 25, 563.G > T were significantly associated with approximately half of the North American SARS‐CoV‐2 isolates that accumulated largely during March 2020. Retrospectively tracing isolates with these two SNPs was used to reconstruct the early, reliable transmission history of North American SARS‐CoV‐2, and European isolates (February 26, 2020) showed transmission 3 days earlier than North American isolates and 17 days earlier than Asian isolates. Collectively, we identified the genetic signatures of the three pairs of coronaviruses and reconstructed an early transmission history of North American SARS‐CoV‐2. We envision that these genetic signatures are possibly diagnosable and predic markers for public health surveillance.